Tax‐Induced Trading: The Effect of the 1986 Tax Reform Act on Stock Market Activity - BOLSTER, PAUL J.; LINDSEY, LAWRENCE B.; MITRUSI, ANDREW (Journal of Finance, 1989)
ABSTRACT The end of favorable tax treatment for long‐term capital gains caused investors to reassess traditional tax‐induced trading strategies. This study compares trading behavior in December 1986 and January 1987 with previous years. Our results indicate that these tax code changes had a powerful effect on trading behavior. Relative trading volume was considerably higher in December 1986 for long‐term winners but not significantly lower for long‐term losers. Results also indicate altered trading patterns based on short‐term gains in December 1986 and for long‐term winners in January 1987.